Smart Online Photoshop - Hawa Osama; Hiba Ghannam (My University, 2011)
In this project we devoted our work to develop an online web application for graphics and image editing. This Smart Online Photoshop is a smart client, meaning that it provides a good performance without needing to contact the server. Smart also means that you can continue working in the event of an interruption of the internet service, so it is an offline application. For application functionality you can choose your photo and start editing it using filters, crop, add shapes, change colors, add backgrounds and duplicate any element you want by copying and pasting that selected element. Also, you can draw any thing you need, fill colors, and add different brushes. When using the application you will see many different and interesting tools and you can save anything you want with any image extension.

In this project we devoted our work to develop an online web application for graphics and image editing. This Smart Online Photoshop is a smart client, meaning that it provides a good performance without needing to contact the server. Smart also means that you can continue working in the event of an interruption of the internet service, so it is an offline application. For application functionality you can choose your photo and start editing it using filters, crop, add shapes, change colors, add backgrounds and duplicate any element you want by copying and pasting that selected element. Also, you can draw any thing you need, fill colors, and add different brushes. When using the application you will see many different and interesting tools and you can save anything you want with any image extension.
Smart Online Photoshop